2009
DOI: 10.1016/j.alcohol.2008.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Excessive alcohol consumption is blocked by glial cell line–derived neurotrophic factor

Abstract: We previously found that activation of the glial cell line–derived neurotrophic factor (GDNF) pathway in the ventral tegmental area (VTA) reduces moderate alcohol (ethanol) intake in a rat operant self-administration paradigm. Here, we set out to assess the effect of GDNF in the VTA on excessive voluntary consumption of ethanol. Long–Evans rats were trained to drink large quantities of a 20% ethanol solution in an intermittent-access two-bottle choice drinking paradigm. The rats were given three 24-h sessions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
154
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(165 citation statements)
references
References 58 publications
6
154
2
1
Order By: Relevance
“…En este concreto, los animales reciben tres sesiones de 24 horas con un libre acceso a ambas botellas (una de alcohol y otra de agua) por semana (típicamente lunes, miércoles y viernes), con 24 y 48 horas de abstinencia durante los días entre semana y los fines de semana respectivamente, recibiendo en los períodos de abstinencia dos botellas de agua (y ninguna de alcohol). Para contrarrestar la variable del aprendizaje de lugar se alterna la colocación de las botellas en cada sesión de exposición al alcohol (Barak, Carnicella, Yowell y Ron, 2011;Carnicella, Amamoto y Ron, 2009;Giuliano et al, 2015). Para determinar su preferencia por la sustancia de abuso, el volumen de alcohol y el de agua son cuantificados cada día.…”
Section: Modelos De Consumo Libreunclassified
“…En este concreto, los animales reciben tres sesiones de 24 horas con un libre acceso a ambas botellas (una de alcohol y otra de agua) por semana (típicamente lunes, miércoles y viernes), con 24 y 48 horas de abstinencia durante los días entre semana y los fines de semana respectivamente, recibiendo en los períodos de abstinencia dos botellas de agua (y ninguna de alcohol). Para contrarrestar la variable del aprendizaje de lugar se alterna la colocación de las botellas en cada sesión de exposición al alcohol (Barak, Carnicella, Yowell y Ron, 2011;Carnicella, Amamoto y Ron, 2009;Giuliano et al, 2015). Para determinar su preferencia por la sustancia de abuso, el volumen de alcohol y el de agua son cuantificados cada día.…”
Section: Modelos De Consumo Libreunclassified
“…Activation of TrkB in the hippocampus contributes to late phase long-term potentiation (Messaoudi et al, 2002;Lu et al, 2008;Minichiello, 2009;Panja and Bramham, 2014), whereas hippocampal p75NTR enhances long-term depression (Woo et al, 2005). In addition, TrkB mediates neuronal survival (Andero et al, 2014;Deinhardt and Chao, 2014), whereas p75NTR was reported to induce apoptosis (Woo et al, 2005). Finally, TrkB and p75NTR play opposing roles in fear acquisition and anxiety in mice (Olsen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF ligation with the receptor tyrosine kinase tropomyosin receptor kinase B (TrkB) results in the activation of the receptor and in the corresponding activation of the phosphatidylinositol-3-kinase, and/or phospholipase C and/or the mitogen activated protein kinase (MAPK) pathways that in turn initiate transcription and/or translation events (Patapoutian and Reichardt, 2001;Yoshii and Constantine-Paton, 2010;Andero et al, 2014). In addition to binding to TrkB, BDNF, like other neurotrophins, can also interact, albeit with lower affinity, with the p75 neurotrophin receptor (p75NTR), a member of the tumor necrosis factor receptor superfamily (Dechant and Barde, 2002;Kraemer et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Glial cell line-derived neurotrophic factor (GDNF) is a protein that is essential for the maintenance and survival of dopamine (DA) neurons (Boger et al, 2006) and can inhibit microglial activation (Rocha, Cristovão, Campos, Fonseca, & Baltazar, 2012). Additionally, preclinical evidence suggests that infusion of GDNF into the ventral tegmental area (VTA) blocks the acquisition and expression of alcohol-induced conditioned place preference (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011;Barak, Carnicella, Yowell, & Ron, 2011), rapidly reduces alcohol intake (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009, Carnicella, Amamoto, & Ron, 2009Carnicella, Kharazia, Jeanblanc, Janak, & Ron, 2008), and blocks alcohol reinstatement following extinction (Carnicella et al, 2008). Furthermore, endogenous levels of GDNF have been found to negatively regulate the rewarding effect of alcohol after a period of abstinence (Carnicella, Ahmadiantehrani, et al, 2009;Carnicella, Amamoto, et al, 2009).…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%
“…Additionally, preclinical evidence suggests that infusion of GDNF into the ventral tegmental area (VTA) blocks the acquisition and expression of alcohol-induced conditioned place preference (Barak, Ahmadiantehrani, Kharazia, & Ron, 2011;Barak, Carnicella, Yowell, & Ron, 2011), rapidly reduces alcohol intake (Carnicella, Ahmadiantehrani, Janak, & Ron, 2009, Carnicella, Amamoto, & Ron, 2009Carnicella, Kharazia, Jeanblanc, Janak, & Ron, 2008), and blocks alcohol reinstatement following extinction (Carnicella et al, 2008). Furthermore, endogenous levels of GDNF have been found to negatively regulate the rewarding effect of alcohol after a period of abstinence (Carnicella, Ahmadiantehrani, et al, 2009;Carnicella, Amamoto, et al, 2009). In one human study, GDNF serum levels measured peripherally were found to be significantly reduced in alcohol-dependent patients versus healthy controls and to be negatively associated with measures of tolerance and withdrawal (Heberlein et al, 2010).…”
Section: Neuroinflammation and Alcohol Dependencementioning
confidence: 99%